Hyperoside: A review on its sources, biological activities, and molecular mechanisms - Wang, Qi; Wei, Hao‐Cheng; Zhou, Sheng‐Jun; Li, Ying; Zheng, Ting‐Ting; Zhou, Chang‐Zheng; Wan, Xin‐Huan (Phytotherapy research, 2022)
Hyperoside is a natural flavonol glycoside in various plants, such as Crataegus pinnatifida Bge, Forsythia suspensa, and Cuscuta chinensis Lam. Medical research has found that hyperoside possesses a broad spectrum of biological activities, including anticancer, anti‐inflammatory, antibacterial, antiviral, antidepressant, and organ protective effects. These pharmacological properties lay the foundation for its use in treating multiple diseases, such as sepsis, arthritis, colitis, diabetic nephropathy, myocardial ischemia–reperfusion, pulmonary fibrosis, and cancers. Hyperoside is obtained from the plants and chemical synthesis. This study aims to provide a comprehensive overview of hyperoside on its sources and biological activities to provide insights into its therapeutic potential, and to provide a basis for high‐quality studies to determine the clinical efficacy of this compound.